Economics of climate change: Introducing the Basic Climate Economic (BCE) model - Lucas Bretschger; Christos Karydas (ETH Zurich, CER-ETH - Center of Economic Research, 2018)
The paper develops the Basic Climate Economic (BCE) model featuring the core elements of climate economics and climate policy. The BCE model incorporates fossil stock depletion, pollution stock accumulation, endogenous growth, and climate-induced capital depreciation. We first use graphical analysis to show the effects of climate change and climate policy on economic growth. Intuition for the different model mechanisms, the functional forms, and the effects of different climate policies is provided. We then show the model equations in mathematical terms to derive closed-form solutions and to run model simulations relating to the graphical part. Finally, we compare our setup to other models of climate economics.
Keywords: Q43; O47; Q56; O41; 330; Climate change; endogenous growth; climate policy; resource use; stock pollution